Laryngeal amyloidosis: a case report - Alswaiheb, Jameel N.; Motiwala, Mohammed A.; Alkhodair, Abdulmalik; Aljadoa, Abdulrahman; Alhindi, Ghada; Cletus, Jose (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Amyloidosis is a rare, benign, slowly progressive disease characterized by extracellular accumulation of amyloid in different tissues of the body. It accounts for 0.2-1.2% of benign laryngeal tumors and usually presents as an isolated localized laryngeal amyloidosis, but can also be part of systemic amyloidosis. A 26 years old female with history of gradually developing, persistent hoarseness, and progressive dyspnea since 1 year, worsened over the past three days. Outpatient Department based endoscopy showed bilateral mobile, thickened vocal cords with subglottic edematous thickness. Computed tomography scan showed symmetrical thickening of bilateral vocal cord, causing glottic narrowing about 70% on the AP view and about 50% on the lateral view and no cartilage invasion or lymphadenopathy. Microlaryngoscopy and biopsy of the specimen were performed and histopathology confirmed the diagnosis of amyloidosis with Congo red stain. Patient was managed by surgical excision of the mass and long term follow-up. To rule out systemic amyloidosis patient is referred to rheumatology clinic and hematology clinic for further evaluation and management. Histopathological examination of the involved tissue confirms the diagnosis, and long term follow up is mandatory in the management of amyloidosis.